Pengaruh Beban Kerja, Stres Kerja, Dan Kepuasan Gaji Terhadap Turnover Intention Karyawan Pada PT. Beringin Gigantara KC Surabaya - Dian Mega Pratiwi; Hadi Sunaryo; Budi Wahono (UNIVERSITAS ISLAM MALANG, 2020)
Abstract This study aims to describe the workload, work stress, salary satisfaction and employee turnover intention of PT. Bringin Gigantara KC Surabaya, knowing the effect of workload, work stress, salary satisfaction on employee turnover intention. This research was conducted at PT. Bringin Gigantara KC Surabaya with a sample size of 50 respondents. The data analysis technique uses multiple linear regression analysis. Descriptive analysis results show that the employees of PT. Bringin Gigantara perceives agreeing on all research variables namely workload, work stress, salary satisfaction and turnover intention. Workload has a significant effect on employee turnover intention of PT. Bringin Gigantara. Job stress has a significant effect on employee turnover intention of PT. Bringin Gigantara. Salary satisfaction has a significant effect on employee turnover intention of PT. Bringin Gigantara. Workload, work stress, and salary satisfaction simultaneously have a significant effect on employee turnover intention of PT. Bringin Gigantara KC Surabaya. Keywords: workload, job stress, salary satisfaction and employee turnover intention.